PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA - anto, yusri; Yanto, Agus Defri (SCIENTIA JOURNAL, 2021)
The development of financial accounting research related to the ups and downs of circulating stock prices illustrates a company's strength to compete in the business world. In this research, researchers aim to determine the impact of profitability, liquidity and leverage on stock prices. This research is a quantitative study. The population in this survey is for the 2015-2019 listed food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling method used is a targeted sampling method with different predetermined criteria, there are 9 production companies in the food and beverage sub-sector. The research period is 2015-2019 or 5 years. Testing the hypothesis in this research using the method of multiple linear regression analysis using statistical statistical application for social sciences (SPSS) version 20.0 as a testing tool. Based on the yield of simultaneous tests that the variable profitability, liquidity and leverage have a significant impact on share prices. And the partial test results show that profitability and leverage variables have a significant positive impact on stock prices, while the liquidity variable has no significant impact on stock prices.